2006
DOI: 10.1371/journal.pmed.0030046
|View full text |Cite
|
Sign up to set email alerts
|

Excess Circulating Angiopoietin-2 May Contribute to Pulmonary Vascular Leak in Sepsis in Humans

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is a devastating complication of numerous underlying conditions, most notably sepsis. Although pathologic vascular leak has been implicated in the pathogenesis of ARDS and sepsis-associated lung injury, the mechanisms promoting leak are incompletely understood. Angiopoietin-2 (Ang-2), a known antagonist of the endothelial Tie-2 receptor, was originally described as a naturally occurring disruptor of normal embryonic vascular development otherwise mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
479
3
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 459 publications
(525 citation statements)
references
References 58 publications
35
479
3
7
Order By: Relevance
“…In fact, angiopoietin 2 release has been shown to be responsible for the sepsis-induced leakage of pulmonary blood vessels. 25 It was also suggested that angiopoietin 2 participates in the recruitment of bone marrow-derived endothelial precursors, as well as stimulates EPC migration. 26,27 It is quite possible that the observed recruitment of stem cells in our studies represents another facet of the same phenomenon-the stress-induced response.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, angiopoietin 2 release has been shown to be responsible for the sepsis-induced leakage of pulmonary blood vessels. 25 It was also suggested that angiopoietin 2 participates in the recruitment of bone marrow-derived endothelial precursors, as well as stimulates EPC migration. 26,27 It is quite possible that the observed recruitment of stem cells in our studies represents another facet of the same phenomenon-the stress-induced response.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Since sepsis is characterized by vascular leakage, Ang2 has also been implicated in this condition in humans. 57,58 …”
Section: Angiopoietinmentioning
confidence: 99%
“…A systemic increase in permeability, leading to a degree of vascular leak that impairs organ function, is a hallmark of sepsis, a lethal syndrome of multiorgan dysfunction that arises as a result of disseminated infection. We have previously shown that Tie-2 inhibition induces changes in the endothelial cytoskeleton that are mediated by the small GTPase RhoA and lead to increased cell contraction and enhanced vascular permeability (7). These experiments suggest that the anti-permeability effect of activated Tie-2 may depend on endothelial cytoskeletal forces and cell architecture.…”
mentioning
confidence: 92%